Formulation and evaluation of a gastroretentive drug delivery system of ranitidine hydrochloride - Nkuna, Princess (My University, 2019)
Various approaches have been developed to retain dosage forms in the gastrointestinal tract. One of the commonly used approaches is the use of microspheres. Due to their intrinsic low density and small size, they are distributed throughout the gastrointestinal tract which improves drug absorption thus improving bioavailability. Ranitidine hydrochloride, an antiulcer drug is poorly absorbed from the lower gastrointestinal tract and has a short half-life of 2.5-3 hours. The aim of this study was to formulate and evaluate gastroretentive microspheres of ranitidine hydrochloride in order to extend gastric retention in the upper gastrointestinal tract, which may result in enhanced absorption and thus improved bioavailability. Pre-formulation studies were conducted to develop and validate the analytical method to identify and quantify ranitidine hydrochloride; to select the suitable polymers for further formulation development and; to determine the compatibility of the chosen polymers with ranitidine hydrochloride. The analytical method was validated and found to be sensitive, linear, precise and accurate. Preliminary formulations lead to the selection of ethyl cellulose and PEG 4000 as polymers and solvent evaporation as the method of manufacture. Compatibility studies were determined by DSC/TGA, FTIR and short-term accelerated studies and no incompatibilities were observed. Two prototype formulations of the preliminary formulations F24 and F26 were manufactured comprised of varying drug: polymer concentration. The microspheres were evaluated for morphology, particle size, flow properties, percentage yield, buoyancy and in vitro drug release. Both formulations resulted in spherical microspheres with good flow properties, high yield and buoyancy studies revealed that the microspheres would float immediately upon contact with the dissolution media and floating would continue for more than 8 hours. In vitro drug release studies revealed that polymer concentration greatly affected drug release. Dissolution kinetic studies revealed that formulation F24 and v F26 were best described by the Korsmeyer-Peppas and Higuchi kinetic models respectively. Formulation F26 was considered the best formulation, which comprised of a drug: PEG 4000 ratio of 1:2 w/w, as it yielded better in better drug encapsulation, better buoyancy results and had complete drug release.
Thesis (M. Pharm. (Pharmaceutics)) -- University of Limpopo, 2019
Keywords: Ranitidine hydrochloride; Microspheres; Ethyl cellulose; PEG 4000; Ranitidine; Drug delivery systems; Microspheres (Pharmacy)